Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài
Nguyễn Vũ  Hoang

58-2.x=63-x

58-2.x=63-x

=> -2x + x = 63 - 58

=> -x = 5

=> x = -5

vậy ...

Khách vãng lai đã xóa
bui hung luong
18 tháng 3 2020 lúc 20:38

-2x+x=63-58

-1x=5

=>1x=-5

x=-5

Khách vãng lai đã xóa
bui hung luong
18 tháng 3 2020 lúc 20:38

mn nha

Khách vãng lai đã xóa
I am➻Minh
18 tháng 3 2020 lúc 20:38

58-2x = 63-x

-x = 5

x = -5

vậy ... 

Khách vãng lai đã xóa
Huy Hoang
18 tháng 3 2020 lúc 20:41

\(58-2x=63-x\)

\(\Leftrightarrow-2x+x=63-58\)

\(\Leftrightarrow-x=5\)

\(\Leftrightarrow x=-5\)

Vậy :.....................

Khách vãng lai đã xóa
Emma
18 tháng 3 2020 lúc 20:42

58 - 2.x = 63 - x

-2 . x + x = 63 - 58

-x = 5

\(\Leftrightarrow\)x = -5

Vậy x = -5

~ HOK TỐT ~

Khách vãng lai đã xóa
Ánh Tuyết
19 tháng 3 2020 lúc 8:03

58 - 2x = 63 - x

<=> -2x + x = 63 - 58

<=> -x = 5

<=> x = -5

Vậy x = -5

Khách vãng lai đã xóa

Các câu hỏi tương tự
phamthiminhtrang
Xem chi tiết
Trang Ngân
Xem chi tiết
Mạc Thị Thu Hiền
Xem chi tiết
Xem chi tiết
lê quyên thảo
Xem chi tiết
Nguyen Ngoc Uyen Phuong
Xem chi tiết
Đặng Phương Thảo
Xem chi tiết
Nguyễn Ngọc Điệp
Xem chi tiết
Hoàng Lê Văn Trung
Xem chi tiết